The RNA of RNase MRP is required for normal processing of ribosomal RNA. - Chu, S (1994)
We have isolated clones which complement the temperature sensitivity and abnormal rRNA processing pattern of the rrp2-2 mutant of Saccharomyces cerevisiae we previously described. DNA sequencing and restriction analysis demonstrated that all clones contain the NME1 gene encoding the RNA of the ribonucleprotein particle RNase MRP. Deletion analysis showed that the NME1 gene is responsible for the complementation of the rrp2-2 phenotype. A single base change was identified in the nme1 gene in the rrp2 mutant, confirming that the RRP2 and NME1 genes are identical. Our experiments therefore indicate that RNase MRP, in addition to its previously reported role in formation of RNA primers for mitochondrial DNA replication [Clayton, D. A. (1991) Trends Biochem. Sci. 16, 107-111], is involved in rRNA processing.